Reconstructing Islamic Tolerance and Its Implications for Islamic Religious Education Learning - Intan Nur Fauziyah Amaliyah; Muhammad Suyudi; Ahmad Yusam Thobroni (Mozaic : Islam Nusantara, 2026)
The plurality of modern society demands a more contextual understanding of tolerance within Islamic teachings. However, in practice, the concept of tolerance is often understood disproportionately, either in the form of exclusivism that limits social interaction or permissivism that blurs theological boundaries. This study aims to reconstruct the concept of tolerance in Islam in a pluralistic society and analyze its implications for Islamic Religious Education (PAI) learning. This study uses a literature review approach with a narrative literature review model. Data sources include primary and secondary literature consisting of national and international journal articles and research reports relevant to the topics of tolerance in Islam, pluralistic society, and religious education. This study uses a literature review approach with a narrative literature review model. Data were obtained from journal articles, academic books, and research reports through the Google Scholar, SINTA, and DOAJ databases with publication priorities for the last ten years. The analysis was conducted using content analysis techniques through the stages of identification, classification, and synthesis of concepts. The results of the study indicate that tolerance (tasāmuh) in Islam is not only based on the Qur'an and hadith, but also requires active involvement in building just and harmonious social relations. This study formulates the reconstruction of tolerance as a shift from passive tolerance to active-participatory tolerance that emphasizes the balance between theological commitment and social responsibility. The implication is that Islamic Religious Education learning needs to be developed in a dialogical, reflective, and contextual manner to foster a tolerant attitude in a pluralistic society.